Prophetic Medication Al-hijamah (Hijamah) and Approach of Kashmiri People Towards Hijamah Cupping Therapy: An Empirical Study - Bilal Ahmad Bhat; Syed Sabahat Ashraf; Shafia Jan; Bilkees Nazir; Intizar Ahmad; Arshi Rafiq (Penerbit Hellow Pustaka, 2024)
Worldwide cupping therapy is used and in Islam term Al-hijamah (Hijamah) also called as prophetic medicine is used in place of cupping therapy. Holy Prophet Muhammad (Peace be upon him ) said, the best among your treatments is Al-hijamah (Hijamah) as it is a promising excretory treatment to clear blood of causative pathological substances. It is a three-step iron excretion technique (skin suction, scarification and suction) through pressure-dependent filtration then excretion via the skin dermal capillaries that significantly decreased serum iron overload and accompanying oxidative stress by exploitation of physiological excretory mechanism. In current study, 200 patients (100 male and 100 female) from various Unani Hospitals of Kashmir were selected at random for our study on their consent. The study revealed that majority of the respondents understudy were aware of the benefits of Hijamah and there was nonsignificant difference in general between male and female respondents (P>0.05). Hijama is used to treat diseases such as high blood pressure, lower back pain, shingles pain, facial paralysis, spinal disk wear and tear (cervical spondylosis), cardiovascular disease prevention, neck pain, musculoskeletal pain, fibromyalgia, carpal tunnel syndrome, headache, migraine, cellulitis, cough, cold, asthma, acne, urticaria, neurodermatitis, soft tissue injury, arthritis. Practitioners apply the cups to different parts of the body of an individual such as neck,back, between the shoulders, behind the ear, chin, thighs, middle and crown of the head, ankle joints, knee joints, breast, buttocks, wrist joints, hips. Finally, researchers gave the suggestions for the effective use of Hijamah.